2023
DOI: 10.3390/foods12203778
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrothermal Treatment of Brewer’s Spent Grain on the Concentration and Molecular Weight Distribution of 1,3-1,4-β-D-Glucan and Arabinoxylan

Julia Steiner,
Michael Kupetz,
Thomas Becker

Abstract: Brewer’s spent grain (BSG) is the most abundant residual in the brewing process. Non-starch polysaccharides such as 1,3-1,4-β-D-glucan (β-glucan) and arabinoxylan (AX) with proven beneficial effects on human health remain in this by-product in high amounts. Incorporating the valuable dietary fiber into the food industry could contribute to a healthy diet. However, a major challenge is extracting these dietary fibers (i.e., β-glucan and AX) from the solid residue. In this study, hydrothermal treatment (HT) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…However, at the higher product purity obtained in this study, the extraction yield (0.057%, w/w) was significantly lower than that reported in [8] (13%, w/w). A much higher extraction yield and recovery yield of β-glucan of 0.63% (w/w) and 85.1% (w/w), respectively were obtained by hydrothermal treatment of BSG at 160 • C, 2 min, and a pressure of 20 bar [4]. However, most of the extracted β-glucan (more than 80%) was degraded to smaller molecules with a molecular weight of less than 50 kDa, which is undesirable as it has less health-promoting effect [18].…”
Section: Effect Of Temperature and Time On β-Glucan Extractionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, at the higher product purity obtained in this study, the extraction yield (0.057%, w/w) was significantly lower than that reported in [8] (13%, w/w). A much higher extraction yield and recovery yield of β-glucan of 0.63% (w/w) and 85.1% (w/w), respectively were obtained by hydrothermal treatment of BSG at 160 • C, 2 min, and a pressure of 20 bar [4]. However, most of the extracted β-glucan (more than 80%) was degraded to smaller molecules with a molecular weight of less than 50 kDa, which is undesirable as it has less health-promoting effect [18].…”
Section: Effect Of Temperature and Time On β-Glucan Extractionmentioning
confidence: 98%
“…In addition, our study showed that the extraction of β-glucan using hot water resulted in higher β-glucan purity (59.8%, w/w) compared to the hydrothermal extraction (0.63%, w/w). The low product purity could be due to the fact that the β-glucan was not purified from the BSG hydrolysates [4]. Steiner et al [4] illustrated that the arabinoxylan in the extract from hydrothermal treatment of BSG was nearly 30 times higher than that of β-glucan.…”
Section: Effect Of Temperature and Time On β-Glucan Extractionmentioning
confidence: 99%
See 3 more Smart Citations